Comparative analysis of ribosomal proteins in complete genomes: an example of reductive evolution at the domain scale - Lecompte, Odile (Oxford University Press, 2002)
A comprehensive investigation of ribosomal genes in complete genomes from 66 different species allows us to address the distribution of r-proteins between and within the three primary domains. Thirty-four r-protein families are represented in all domains but 33 families are specific to Archaea and Eucarya, providing evidence for specialisation at an early stage of evolution between the bacterial lineage and the lineage leading to Archaea and Eukaryotes. With only one specific r-protein, the archaeal ribosome appears to be a small-scale model of the eukaryotic one in terms of protein composition. However, the mechanism of evolution of the protein component of the ribosome appears dramatically different in Archaea. In Bacteria and Eucarya, a restricted number of ribosomal genes can be lost with a bias toward losses in intracellular pathogens. In Archaea, losses implicate 15% of the ribosomal genes revealing an unexpected plasticity of the translation apparatus and the pattern of gene losses indicates a progressive elimination of ribosomal genes in the course of archaeal evolution. This first documented case of reductive evolution at the domain scale provides a new framework for discussing the shape of the universal tree of life and the selective forces directing the evolution of prokaryotes.